Pengaruh Harga Dan Biaya Produksi Terhadap Pendapatan Petani Karet Di Desa Sungai Rambut Kecamatan Berbak Kabupaten Tanjung Jabung Timur - Rika Andriani; Titin Agustin Nengsih; Ahmad Syukron Prasaja (JOURNAL SAINS STUDENT RESEARCH, 2023)
Rubber is a plantation commodity that has high economic value and is valuable in the strategy of increasing the income of farmers. Many people in Sungai Rambut Village rely on income from rubber plantations for their daily needs. Prices and Production Costs are important factors in farmer income, where the right price will be able to increase farmer income and of course with low production costs in accordance with the income received by farmers. The purpose of this study was to find out how much influence price and production costs have on the income of rubber farmers in Sungai Rambut Village, Berbak District, Tanjung Jabung Timur Regency. Berbak District, East Tanjung Jabung Regency. (2) Production costs have a positive and significant effect on the income of rubber farmers in Sungai Rambut Village, Berbak District, East Tanjung Jabung Regency. (3) Prices and production costs have a simultaneous effect on the income of rubber farmers in Sungai Rambut Village, Berbak District, East Tanjung Jabung Regency.